2019
DOI: 10.1186/s13019-019-0871-5
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial closure with extracellular matrix scaffold following cardiac surgery associated with a reduction of postoperative complications and 30-day hospital readmissions

Abstract: BackgroundA prospective, multi-center study (RECON) was conducted to evaluate the clinical outcomes of pericardial closure using a decellularized extracellular matrix (ECM) graft derived from porcine small intestinal submucosa.MethodsPatients indicated for open cardiac surgery with pericardial closure using ECM were eligible for the RECON study cohort. Postoperative complications and readmission of the RECON patients were compared to the patient cohort in the Nationwide Readmissions Database (NRD). Inverse pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Cardiac-derived ECM, obtained by decellularization, has the benefit of conserving the organ-specific ECM architecture and composition and ensuing retention of biochemical cues that favor recellularization ( Kc et al, 2019 ) and has shown promising results in animal models ( Wainwright et al, 2012 ; Sarig et al, 2016 ; Wang et al, 2016 ) and for human applications ( Rego et al, 2019 ). However, decellularized matrices still pose many technical challenges that need to be addressed to meet clinical standards ( Kc et al, 2019 ).…”
Section: Ecm Modulationmentioning
confidence: 99%
“…Cardiac-derived ECM, obtained by decellularization, has the benefit of conserving the organ-specific ECM architecture and composition and ensuing retention of biochemical cues that favor recellularization ( Kc et al, 2019 ) and has shown promising results in animal models ( Wainwright et al, 2012 ; Sarig et al, 2016 ; Wang et al, 2016 ) and for human applications ( Rego et al, 2019 ). However, decellularized matrices still pose many technical challenges that need to be addressed to meet clinical standards ( Kc et al, 2019 ).…”
Section: Ecm Modulationmentioning
confidence: 99%
“…In comparison to the NRD, the RECON outcomes favored PCR and showed statistically significant and clinically significant reductions in hospital readmissions, pleural effusion, pericardial effusion, and bleeding complications. Furthermore, POAF was far less common with PCR than in previously reported studies [Rego 2019].…”
Section: Introductionmentioning
confidence: 59%
“…The majority of studies published since 1995 have utilized a synthetic or biosynthetic pericardial substitute to reconstruct the pericardium. Among studies published since 1995, most reported no increase in complications or a beneficial clinical outcome, such as fewer adhesions by CT scan [Duvernoy 1995], lower rates of postoperative atrial fibrillation (POAF) [Boyd 2010;Kaya 2015;Rego 2019] increased epicardial surface to posterior sternal table distance [Rao 1999], reduced infection [ Kaya 2015], and fewer pericardial effusions [Kaya 2015;Rego 2019]. [Rego 2019].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimizing the incidence When using the CSS approach, the pericardium is opened only over the apex and ascending aorta, preserving the pericardium's physiologic constraint over the entirety of the RV. A recent prospective, multicenter study demonstrated improved outcomes for coronary artery bypass graft (CABG) patients that underwent pericardial closure using a decellularized extracellular matrix graft, including fewer pericardial effusions, fewer postoperative arrhythmias, and fewer 30-day readmissions compared to patients with an unrepaired pericardiotomy (24). More research is needed into the role of the pericardium in LVAD recipients.…”
Section: Discussionmentioning
confidence: 99%